Nigam’s scoring system: a reliable and accurate scoring system to diagnose acute appendicitis - Nigam, Vinod Kumar; Nigam, Siddharth (International Surgery Journal, 2025)
Background: Acute appendicitis is one of the commonest surgical emergencies. The early diagnosis of acute appendicitis is essential and should be treated by appendicectomy at earliest to avoid complications like perforation and gangrene. Various scoring systems are in use for this purpose. Nigam’s scoring system (NSS) is a reliable, easy and accurate scoring system to diagnose acute appendicitis. NSS covers up the shortcomings of other commonly used scoring systems and thus increases its accuracy factor. Methods: NSS is based on clinical features and basic investigations without depending upon advanced investigative techniques such as USG and CT scan. The scoring points in NSS are 17 which are divided into the 3 groups, 6 and less, 7 to 10 and 11 and more. The study includes 72 patients of acute appendicitis between January 2014 and January 2024. The results of operation were compared with histopathological results. Results: Out of 72 patients 4 patients scored 6 and less, 7 patients scored 7 to 10 and 61 patients scored 11 and more. The histopathological reports did not show any normal appendix (negative appendicectomy). Diagnostic accuracy of NSS is found to be 100% correct. Conclusions: NSS is found as the ideal scoring system among available scoring systems due to its 100% accuracy and 0% negative appendicectomy rate (NAR). It is a reliable, simple and accurate scoring system. It requires awareness about NSS among surgeons so can be adopted in various hospitals globally.